Pengaruh Debt To Equity Ratio, Current Ratio, Business Risk, Firm Size, Book Value Terhadap Harga Saham (Studi Kasus Pada Sektor Industri Dasar dan Kimia) - Hantono Hantono; Ike Rukmana Sari; Chiquita Chiquita; Levina Levina; Monica Gloriana; Sabaryanti Sabaryanti (Politeknik Negeri Lampung, 2019)
This study aims to examine the effect of Debt To Equity Ratio, Current Ratio, Business Risk, Firm Size, and Book Value on Stock Prices in companies in the Basic and Chemical Industry sector. This research is quantitative descriptive. The results showed that simultaneously Debt To Equity Ratio, Current Ratio, Business Risk, Firm Size, and Book Value variables had a significant effect on stock prices. Partially, Business Risk variables that use ROE ratios have a significant effect on stock prices. Whereas, the Debt To Equity Ratio, Current Ratio, Firm Size, and Book Value variables do not have a significant effect on stock prices.Keywords: Debt to equity ratio, Current ratio, Business risk, Firm size, Book Value and Stock price.